Formation of Denmark Strait overflow water and its hydro-chemical composition - Tanhua, Toste; Olsson, K. Anders; Jeansson, Emil (Journal of Marine Systems, 2005)
The dense overflow across the Denmark Strait is investigated with hydrographic and hydro-chemical data and the water mass composition of the Denmark Strait Overflow Water (DSOW) is determined by multivariate analysis. Hydrographical properties, the transient tracers CFC-11 and CFC-12, oxygen and nutrients are utilized for the water mass definitions. Distribution and characteristics of water masses north of Denmark Strait are described, the important water masses at the sill and the variability on weekly time-scales are discussed, and the entrainment and mixing of water into the overflow plume in the northern Irminger Basin is calculated. The analysis indicates that water masses both from the Nordic Seas and the Arctic Ocean are important for the formation of DSOW. It is found that water masses transported with the East Greenland Current make up about 75% of the overflow at the sill. The overflow at, and shortly south of, the sill is inhomogeneous with a low-salinity component dominated by Polar Intermediate Water. The high-salinity component of the overflow is mainly of Arctic origin. The water mass composition, and the short-term variability for 7 repeats of sections close to the sill are described, and these illustrate that the overflow is in fact a composite of a number of water masses with different formation and transport histories. This indicate that the overflow is a robust feature, but that it responds to variations in the circulation or atmospheric forcing that influences the formation of intermediate and deep water masses within the Arctic Mediterranean and the North Atlantic. At a section about 400 km south of the sill the overflow is well mixed and modified by entrainment of, mainly, Iceland–Scotland Overflow Water and Labrador Sea Water, together constituting 30% of the overflow plume. The entrainment of Middle Irminger Water dominates shortly downstream of the sill, before the overflow plume reaches too deep but the entrainment seems to be intermittent in time.